Comparative Effectiveness of 755‐nm Picosecond Laser, 755‐ and 532‐nm Nanosecond Lasers for Treatment of Café‐au‐Lait Macules (CALMs): A Randomized, Split‐Lesion Clinical Trial. Issue 4 (8th September 2020) - Cen, Qingqing; Gu, Yifei; Luo, Lan; Shang, Ying; Rao, Yamin; Zhu, Jiafang; Han, Yue; Yu, Wenxin; Liu, Ying; Wu, Xianglei; Ying, Hanru; Ma, Gang; et al.
Abstract : Background and Objectives: Many types of lasers have been used to treat café‐au‐lait macules (CALMs) since the introduction of the selective photothermolysis theory. However, the efficacy and safety of picosecond lasers, compared with those of nanosecond lasers, have not been researched. To compare the efficacy and safety of 755 nm picosecond laser (PS‐755 nm), Q‐switched (QS) Alexandrite 755 nm nanosecond laser (QS‐755 nm), and QS Nd:YAG 532 nm nanosecond laser (QS‐532 nm) for treating CALMs. Study Design/Materials and Methods: Forty‐one patients received several treatments at 3‐month intervals. Lesions were divided into two or three approximately equal parts, which were randomly treated with PS‐755 nm, QS‐755 nm, and QS‐532 nm. The safety and efficacy of three lasers were determined based on blinded visual assessments and self‐reports of patients three months after the comparative trial. Results: Visual assessment 3 months after the comparative trial revealed that there was no statistically significant difference among the sites treated by QS‐755 nm (2.84 ± 1.11), QS‐532 nm (2.63 ± 1.06), and PS‐755 nm (2.74 ± 1.05) lasers. Five (26.32%) of 19 patients showed lesion recurrence. Adverse effects included acneiform miliaris, hypopigmentation, and hyperpigmentation, which were resolved within 12 months. Five (26.32%) of 19 patients who showed lesion recurrence 1–5 months after laser treatment had lightened or cleared at least 50% of the lesion. 46.67% of patients were satisfied or very satisfied with the outcome of the overall treatment. Conclusions: PS‐755 nm, QS‐755 nm, and QS‐532 nm laser treatments were equally effective in treating and improving CALMs. PS‐755 nm caused fewer adverse effects. Individuals can react differently to different types of lasers. Patch tests should be conducted before the treatment. Lasers Surg. Med. © 2020 Wiley Periodicals LLC